Ohmic contacts based on Pd to indium phosphide Gunn diodes - Belyaev, A.E.; Boltovets, N.S.; Bobyl, A.V.; Zorenko, A.V.; Arsentiev, I.N.; Kladko, V.P.; Kovtonyuk, V.M.; Konakova, R.V.; Kudryk, Ya.Ya.; Sachenko, A.V.; Slipokurov, V.S.; Slepova, A.S.; et al. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2015)
Experimental data on manufacturing the ohmic contacts Au–Ti–Pd–n⁺-InP, formed using vacuum deposition of metal onto a heated to 300 °C substrate representing an epitaxial n⁺-n-n⁺⁺-n⁺⁺⁺-InP structure. The specific contact resistance measured at room temperature was about 7·10⁻⁵ Ohm·cm². Voltage-current characteristics within the temperature range 110 to 380 K are linear. Gunn diodes with such contacts, which were made as a straight mesa-structure in a pulsed mode (pulse duration of 100 ns, pulse ratio of 1000, operating current of 2.2 A), generated the microwave power ~10 mW in the V-band.